70 Ensuring Beef's Domestic Market. (10th April 2018) - Butler, J
Abstract: Since its 2015 inception, the U.S. Roundtable for Sustainable Beef (USRSB) has sought to ensure the U.S. beef value chain is the trusted global leader in environmentally sound, socially responsible and economically viable beef. The multi-stakeholder initiative is representative of all sectors of the beef community including cow-calf producers, auction markets, feedyard producers, packers, processors, restaurant owners, food service providers, civil societies, and many other allied industries. The USRSB focuses on advancing, supporting, and communicating continuous improvement of beef sustainability through developed tools: USRSB High Priority Indicators, USRSB Sustainability Metrics, and USRSB Sustainability Assessment Guides. Overreaching categories known as High Priority Indicators recognize areas where the beef supply chain can have a significant sustainability footprint. The USRSB High Priority Indicators include: Land Resources, Employee Safety & Well-being, Efficiency & Yield, Water Resources, Air & Greenhouse Gas Emissions, and Animal Health & Well-being. The USRSB High Priority Indicators were developed to be applicable across all segments of the beef supply chain. USRSB Sustainability Metrics are tools to assess and measure personal progress within corresponding USRSB High Priority Indicators. Unlike USRSB High Priority Indicators, USRSB Sustainability Metrics cannot be applied across all sectors. Each USRSB Sustainability Metric is unique to a segment of the beef supply chain. Development of USRSB Sustainability Metrics was led by individual constituency groups and Allied Industry and Civil Society membership, but included feedback from all other sectors. The USRSB is developing supporting documents to accompany each specific USRSB Sustainability Metric. These documents consist of guidance, descriptions, self-assessment tools, and resource libraries. Collectively, these documents are known as Sustainability Assessment Guides (SAGs). The USRSB embraces the Theory of Change and follows the American National Standards Institute (ANSI)/American Society of Agricultural and Biological Engineers (ASABE) Standard Number 629 Framework to evaluate the sustainability of agricultural production systems. This model was also used throughout the development of USRSB High Priority Indicators, USRSB Sustainability Metrics, and USRSB Sustainability Assessment Guides. In addition, USRSB Sustainability Metrics reflect the SMART model, promoting sustainability efforts that are specific, measurable, achievable, relevant, and time-bound. The entire work-product to date of USRSB, including the USRSB High Priority Indicators, Sustainability Metrics and Sustainability Assessment Guides will be made available for public review in the Spring of 2018.